High-entropy alloy-ceramic composite material and preparation method and application thereof

By covering the metal protective layer on the surface of the ceramic phase powder and the high-entropy alloy layer, combined with vacuum sintering and thermal isostatic pressure seepage treatment, the ceramic phase powder and high-entropy alloy powder in high-entropy alloy composite materials are solved. The uniform mixing and structural stability issues have achieved the preparation of high-performance dense high-entropy alloy-ceramic composites.

CN119287196AActive Publication Date: 2025-01-10XIAMEN TUNGSTEN CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411415652.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Prior Art When preparing high-entropy alloy-ceramic composite materials, it is difficult to mix uniformly between ceramic phase powder and high-entropy alloy powder, and atoms in the ceramic phase are easily dissolved into the liquid phase of high-entropy alloy, resulting in structural damage, resulting in high-entropy alloy. The phase structure is unstable and agglomerated, making it difficult to prepare high-performance composite materials.

Method used

The surface of the ceramic phase powder is coated with a metal protective layer, and a pore presintered body is formed by molding, degreasing and vacuum presintering, and then a high-entropy alloy layer is coated on its surface. Vacuum sintering and thermal isostatic pressure seepage are used to melt it. High-entropy alloys diffuse along pores or interfaces to form dense high-entropy alloy-ceramic composites, controlling the permeability pressure to achieve gradient or uniform distribution.

Benefits of technology

Effectively prevent the damage of ceramic phase atoms to the high-entropy alloy structure, avoid agglomeration, realize the dense distribution and controllable content of the high-entropy alloy phase, improve the performance of composite materials, and solve the defects of traditional powder mixing methods, such as incomplete melting and seepage and size limitations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079420610000141
    Figure BDA0005079420610000141
  • Figure BDA0005079420610000151
    Figure BDA0005079420610000151
Patent Text Reader

Abstract

The invention provides a high-entropy alloy-ceramic composite material and a preparation method and application thereof.The preparation method comprises the steps that the surfaces of particles of ceramic phase powder are coated with a metal protection layer, and a presintered body with the relative density not exceeding 90% is obtained through forming, degreasing and vacuum presintering; and then coating at least two metal layers comprising the innermost high-entropy alloy layer on the surface of the pre-sintered body, and carrying out vacuum sintering, hot isostatic pressing infiltration treatment and annealing treatment to obtain the high-entropy alloy-ceramic composite material. Through the arrangement of the metal protection layer, the damage of carbon, nitrogen, boron or silicon atoms in a ceramic phase to a high-entropy alloy phase structure is prevented; and in cooperation with subsequent hot isostatic pressing infiltration treatment, the problem that a binding phase of the high-entropy alloy is prone to agglomeration due to a traditional powder mixing method is solved, and meanwhile the problems that infiltration is not thorough and is limited by the appearance size of a product are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal-ceramic composite materials, and in particular to a high entropy alloy-ceramic composite material and a preparation method and application thereof. Background Art

[0002] Compared with traditional metal alloys, high entropy alloys have high strength, high toughness, high hardness, high wear resistance, excellent corrosion resistance, and good high temperature stability and high temperature performance. Since the high entropy alloy was proposed, it has been well applied. The high entropy alloy systems that have been developed mainly include the following three categories: light metal high entropy alloy systems based on Al and the fourth and fifth period elements Fe, Co, Ni, Cr, Cu, Mn, Sn, Zn, Li, Mg, Zr and Ti; refractory metal high entropy alloy systems based on refractory metal elements Mo, V, Nb, Hf, Ta, Cr and W; and rare earth metal high entropy alloy systems based on rare earth elements.

[0003] In the field of metal-ceramic composites, due to the excellent performance of high entropy alloys, researchers have tried to use high entropy alloys as metal alloy phases to replace traditional metal alloy phases to further improve the toughness of metal-ceramic composites. However, the preparation of high entropy alloy-ceramic composites by traditional powder metallurgy methods has the following technical difficulties: on the one hand, since the particle size of ceramic phase powders (such as carbides, borides or nitrides) is usually less than 2μm, and ceramic phase powders are easily crushed and refined during ball milling, and ultrafine particle high entropy alloy powders with a particle size of less than 5μm are difficult to mass produce, even if finer high entropy alloy powders can be produced, cold welding between particles is easy to occur during ball milling and agglomeration, based on the above, ceramic phase powders and high entropy alloy powders are difficult to mix evenly by ball milling; on the other hand, during the liquid phase sintering process, atoms such as carbon, boron, nitrogen or silicon in the ceramic phase are easily dissolved in the high entropy alloy liquid phase, and during the cooling process, atoms such as carbon, boron, nitrogen or silicon are easily reacted with the metal components in the high entropy alloy and precipitated, resulting in the destruction of the high entropy alloy phase structure, so that the high entropy alloy cannot play its due role.

[0004] Based on the above analysis, how to obtain a high-performance high-entropy alloy-ceramic composite material in which the high-entropy alloy phase structure is not destroyed, the high-entropy alloy phase is not agglomerated, and the high-entropy alloy phase content is controllable is a problem that needs to be solved urgently in this field. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high entropy alloy-ceramic composite material and a preparation method and application thereof, so as to obtain a high-performance high entropy alloy-ceramic composite material in which the high entropy alloy phase structure is not destroyed, the high entropy alloy phase is not agglomerated, and the high entropy alloy content is controllable.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0008] A metal protective layer is coated on the particle surface of the ceramic phase powder, and then the particles are formed, degreased and vacuum pre-sintered to obtain a pre-sintered body with a relative density not exceeding 90%.

[0009] At least two metal layers are coated on the surface of the pre-sintered body, and then vacuum sintering, hot isostatic pressing infiltration treatment and annealing treatment are performed to obtain the high entropy alloy-ceramic composite material.

[0010] The at least two metal layers include an innermost high entropy alloy layer.

[0011] The temperature T2 of vacuum sintering, the temperature T3 of hot isostatic pressing infiltration treatment and the temperature T4 of annealing treatment are all lower than the melting point T of the metal protective layer. m1 .

[0012] The vacuum sintering temperature T2 is higher than the melting point T m2 .

[0013] The melting point T of the outermost metal layer of the at least two metal layers m3 Higher than the melting point T of the metal protective layer m1 .

[0014] The preparation method provided by the present invention comprises coating a metal protective layer on the particle surface of a ceramic phase powder to prevent atoms such as carbon, nitrogen, boron or silicon in the ceramic phase powder from destroying the phase structure of a high entropy alloy; then forming, degreasing and vacuum pre-sintering are performed to obtain a pre-sintered body with pores; then at least two metal layers including an innermost high entropy alloy layer are uniformly coated on the surface of the pre-sintered body, the surface of the pre-sintered body is sealed by vacuum sintering, and then hot isostatic pressing infiltration treatment is performed to diffuse the molten high entropy alloy into the interior of the pre-sintered body along the pores and / or interfaces of the pre-sintered body, thereby obtaining a dense high entropy alloy-ceramic composite material; wherein, the pressure of the hot isostatic pressing infiltration treatment is controlled to obtain a high entropy alloy-ceramic composite material with a high entropy alloy phase gradient distribution or a high entropy alloy-ceramic composite material with uniform composition; and the application of the hot isostatic pressing infiltration treatment also solves the problem that the high entropy alloy bonding phase is easy to agglomerate due to the traditional powder mixing method, and at the same time, it also solves the problem that the infiltration is not complete and is limited by the product appearance size.

[0015] Preferably, the metal element in the metal protection layer includes any one of Co, Ni or Fe, or a combination of at least two of them.

[0016] Preferably, the melting point of the high entropy alloy layer is m2 It is 600℃-1200℃.

[0017] Preferably, the metal elements in the high entropy alloy layer include a combination of at least five of Al, Fe, Co, Zn, Sn, Ni, Cr, Cu, Mn, Li, Mg or Ti.

[0018] Preferably, the volume of the high entropy alloy layer is not less than the total volume of the pores in the pre-sintered body.

[0019] Preferably, the metal element in the outermost metal layer includes any one of Ti, Zr, Mo, Nb or Ta, or a combination of at least two of them.

[0020] Preferably, the thickness of the outermost metal layer is 0.1 mm-0.3 mm.

[0021] Preferably, the vacuum sintering temperature T2 is higher than the melting point T m2 High 25℃-50℃.

[0022] Preferably, the vacuum sintering temperature T2 is higher than the melting point T m1 Lower than 200℃.

[0023] Preferably, the holding time of the vacuum sintering is 0.5h-1h.

[0024] Preferably, the vacuum sintering pressure is 10 -3 Below Pa.

[0025] Preferably, the hot isostatic pressing infiltration treatment is carried out in an inert atmosphere.

[0026] Preferably, the pressure of the hot isostatic pressing infiltration treatment is 5MPa-300MPa.

[0027] Preferably, the temperature T3 of the hot isostatic pressing infiltration treatment is equal to the temperature T2 of the vacuum sintering.

[0028] Preferably, the heat preservation and pressure holding time of the hot isostatic pressing infiltration treatment is 1h-3h.

[0029] Preferably, the annealing temperature T4 is lower than the melting point T m2 .

[0030] Preferably, the annealing temperature T4 is higher than the melting point T m2 Low 100℃-200℃.

[0031] Preferably, the pressure of the annealing treatment is below 30 Pa.

[0032] Preferably, the temperature is increased from room temperature to the annealing temperature T4 at a heating rate of 0.5°C / min-1°C / min.

[0033] Preferably, the annealing treatment is carried out at a temperature T4 and the holding time is 1 h to 3 h.

[0034] Preferably, the annealing treatment is terminated by cooling the temperature T4 of the annealing treatment to room temperature at a cooling rate of 1°C / min-2°C / min.

[0035] In a second aspect, the present invention provides a high entropy alloy-ceramic composite material, which is prepared by the preparation method described in the first aspect.

[0036] Preferably, when the pressure of the hot isostatic pressing infiltration treatment is greater than 5 MPa and less than 80 MPa, a high-entropy alloy-ceramic composite material with a gradient distribution of high-entropy alloy phase is obtained, that is, the content of the high-entropy alloy phase gradually decreases from the surface to the inside of the high-entropy alloy-ceramic composite material.

[0037] Preferably, when the pressure of the hot isostatic pressing infiltration treatment is higher than 80 MPa and lower than 300 MPa, a high entropy alloy-ceramic composite material with uniform composition is obtained.

[0038] In a third aspect, the present invention provides an application of a high entropy alloy-ceramic composite material, wherein the high entropy alloy-ceramic composite material is used to prepare molds, cutting tools or wear-resistant parts.

[0039] The high entropy alloy-ceramic composite material is prepared by the preparation method described in the first aspect, or is the high entropy alloy-ceramic composite material described in the second aspect.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The preparation method provided by the present invention comprises coating a metal protective layer on the particle surface of a ceramic phase powder to prevent atoms such as carbon, nitrogen, boron or silicon in the ceramic phase powder from destroying the phase structure of a high entropy alloy; then forming, degreasing and vacuum pre-sintering are performed to obtain a pre-sintered body with pores; then at least two metal layers including an innermost high entropy alloy layer are uniformly coated on the surface of the pre-sintered body, the surface of the pre-sintered body is sealed by vacuum sintering, and then hot isostatic pressing infiltration treatment is performed to diffuse the molten high entropy alloy into the interior of the pre-sintered body along the pores and / or interfaces of the pre-sintered body, thereby obtaining a dense high entropy alloy-ceramic composite material; wherein, the pressure of the hot isostatic pressing infiltration treatment is controlled to obtain a high entropy alloy-ceramic composite material with a high entropy alloy phase gradient distribution or a high entropy alloy-ceramic composite material with uniform composition; and the application of the hot isostatic pressing infiltration treatment also solves the problem that the high entropy alloy bonding phase is easy to agglomerate due to the traditional powder mixing method, and at the same time, it also avoids the problem of incomplete infiltration and the limitation of product external dimensions. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0043] A certain embodiment of the present invention provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0044] A metal protective layer is coated on the particle surface of the ceramic phase powder, and then the particles are formed, degreased and vacuum pre-sintered to obtain a pre-sintered body with a relative density not exceeding 90%.

[0045] At least two metal layers are coated on the surface of the pre-sintered body, and then vacuum sintering, hot isostatic pressing infiltration treatment and annealing treatment are performed to obtain the high entropy alloy-ceramic composite material.

[0046] The at least two metal layers include an innermost high entropy alloy layer.

[0047] The temperature T2 of vacuum sintering, the temperature T3 of hot isostatic pressing infiltration treatment and the temperature T4 of annealing treatment are all lower than the melting point T of the metal protective layer. m1 .

[0048] The vacuum sintering temperature T2 is higher than the melting point T m2 .

[0049] The melting point T of the outermost metal layer of the at least two metal layers m3 Higher than the melting point T of the metal protective layer m1 .

[0050] The preparation method provided by the present invention comprises coating a metal protective layer on the particle surface of a ceramic phase powder to prevent atoms such as carbon, nitrogen, boron or silicon in the ceramic phase powder from destroying the phase structure of a high entropy alloy; then forming, degreasing and vacuum pre-sintering are performed to obtain a pre-sintered body with pores; then at least two metal layers including an innermost high entropy alloy layer are uniformly coated on the surface of the pre-sintered body, the surface of the pre-sintered body is sealed by vacuum sintering, and then hot isostatic pressing infiltration treatment is performed to diffuse the molten high entropy alloy into the interior of the pre-sintered body along the pores and / or interfaces of the pre-sintered body, thereby obtaining a dense high entropy alloy-ceramic composite material; wherein, the pressure of the hot isostatic pressing infiltration treatment is controlled to obtain a high entropy alloy-ceramic composite material with a high entropy alloy phase gradient distribution or a high entropy alloy-ceramic composite material with uniform composition; and the application of the hot isostatic pressing infiltration treatment also solves the problem that the high entropy alloy bonding phase is easy to agglomerate due to the traditional powder mixing method, and at the same time, it also avoids the problem of incomplete infiltration and the limitation of product external dimensions.

[0051] In the present invention, there is no specific restriction on the vacuum pre-sintering temperature T1. It is only necessary to make the relative density of the pre-sintered body not exceed 90%, that is, to control the total volume of the pores in the pre-sintered body, and further control the content of the high entropy alloy phase in the high entropy alloy-ceramic composite material.

[0052] The relative density of the pre-sintered body in the present invention refers to the ratio of the density of the pre-sintered body to the theoretical density of the metal-ceramic composite material composed of the ceramic phase powder and the metal protective layer.

[0053] In some embodiments, the relative density of the pre-sintered body is also related to the initial relative density of the molded body. Generally, the relative density of the molded body after molding is not less than 35%.

[0054] In certain embodiments, the raw material powder of the ceramic phase powder includes more than 50 vol % of the ceramic phase raw material and less than 50 vol % of the additive powder, measured in volume percentage.

[0055] In certain embodiments, the ceramic phase powder comprises any one of nitride ceramic phase powder, boride ceramic phase powder or carbide ceramic phase powder, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of nitride ceramic phase powder and boride ceramic phase powder, a combination of nitride ceramic phase powder and carbide ceramic phase powder, or a combination of nitride ceramic phase powder, boride ceramic phase powder and carbide ceramic phase powder.

[0056] In certain embodiments, the nitride ceramic phase powder includes any one of TiCN, AlN, TiN, SiAlON or BN, or a combination of at least two thereof.

[0057] In some embodiments, when the ceramic phase powder is a nitride ceramic phase powder, the additive powder includes WC, Cr3C2, VC, ZrC, TiC, Mo2C, TaC, NbC, SiC, SiC w Any one of whiskers, B4C, ZrB, ZrB2, TiB, TiB2, WB, W2B, W2B5, CrB, ZrN, TiN or rare earth metal borides, or a combination of at least two thereof.

[0058] In certain embodiments, the boride ceramic phase powder includes ZrB2 and / or TiB2.

[0059] In some embodiments, when the ceramic phase powder is a boride ceramic phase powder, the additive powder includes WC, Cr3C2, VC, ZrC, TiC, TiCN, Mo2C, TaC, NbC, SiC, SiC w Any one of whiskers, B4C, ZrB, TiB, WB, W2B, W2B5, CrB, SiAlON, BN, AlN, ZrN, TiN or rare earth metal borides, or a combination of at least two thereof.

[0060] In certain embodiments, the carbide ceramic phase powder includes any one of TiC, ZrC, SiC or B4C or a combination of at least two thereof.

[0061] In some embodiments, when the ceramic phase powder is a carbide ceramic phase powder, the additives include WC, Cr3C2, VC, Mo2C, TaC, NbC, SiC w Any one of whiskers, ZrB, ZrB2, TiB, TiB2, WB, W2B, W2B5, CrB, SiAlON, BN, AlN, ZrN, TiCN, TiN or rare earth metal borides, or a combination of at least two thereof.

[0062] In certain embodiments, the preparation method of the ceramic phase powder includes: placing a formulated amount of ceramic phase matrix powder, additive powder and grinding balls in a ball mill, injecting anhydrous ethanol into the ball mill, and ball milling and mixing in a protective atmosphere for more than 24 hours to obtain a uniformly mixed ceramic phase powder.

[0063] In some embodiments, the material of the grinding balls used in the ball milling mixture includes silicon carbide, silicon nitride or cemented carbide balls, and the mass ratio of the grinding balls to the raw material powder is 2:1-8:1, for example, it can be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1, but is not limited to the listed values, and the remaining values ​​not listed in the numerical range are also applicable.

[0064] In some embodiments, the protective gas during the ball milling mixing includes nitrogen and / or an inert gas, wherein the inert gas includes any one of helium, neon or argon, or a combination of at least two of them.

[0065] In certain embodiments, the method of coating the metal protective layer on the surface of the ceramic phase powder particles includes chemical plating.

[0066] In some embodiments, the chemical coating method includes the following steps: activating the ceramic phase powder with an activation solution, placing it in a chemical plating solution for chemical coating, and then washing and vacuum drying to complete the chemical coating.

[0067] In some embodiments, the activation solution includes hydrofluoric acid (mass percentage concentration is 40wt%), ammonium fluoride, nitric acid (mass percentage concentration is 65wt%) and hydrochloric acid (mass percentage concentration is 36wt%); wherein the amounts of hydrofluoric acid, ammonium fluoride, nitric acid and hydrochloric acid in the activation solution are 30mL / L-50mL / L, 2g / L-4g / L, 20mL / L-40mL / L and 10mL / L-30mL / L, respectively.

[0068] The present invention removes impurities on the surface of ceramic phase powder particles by activation, and at the same time modifies the microstructure of the surface of ceramic phase powder particles, so that micro defects such as active stacking faults or dislocations are generated on the surface of ceramic phase powder particles, thereby helping to induce the deposition of bonding phase metal ions on the particle surface and improve the bonding strength.

[0069] In certain embodiments, the activation comprises ultrasonic stirring for 15 min-30 min, for example, 15 min, 20 min, 25 min or 30 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0070] In some embodiments, the solid-liquid ratio during chemical plating is 150g / L-1500g / L, for example, it can be 150g / L, 300g / L, 500g / L, 800g / L, 1000g / L, 1200g / L or 1500g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some embodiments, the chemical plating solution includes 20g / L-30g / L of a protective metal salt compound, 20g / L-30g / L of a reducing agent, 40g / L-60g / L of a complexing agent, and 20g / L-30g / L of a stabilizer.

[0072] In certain embodiments, the protective metal salt compound comprises a protective metal sulfate compound and / or a protective metal chloride compound.

[0073] In some embodiments, the protective metal salt compound includes any one of a cobalt salt compound, a nickel salt compound, or an iron salt compound, or a combination of at least two thereof.

[0074] In certain embodiments, the reducing agent comprises sodium hypophosphite.

[0075] In certain embodiments, the complexing agent comprises trisodium citrate.

[0076] In certain embodiments, the stabilizer comprises boric acid.

[0077] In some embodiments, the chemical coating is carried out under ultrasonic stirring at a temperature of 40°C-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] In some embodiments, during the chemical coating process, the vacuum drying temperature is 60°C-120°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In the present invention, the metal elements in the metal protective layer need to have good compatibility with the ceramic phase powder, so as to improve the interface strength between the metal protective layer and the ceramic phase powder; the metal protective layer is also required to have good compatibility with the high entropy alloy phase, so as to facilitate the infiltration of the high entropy alloy during hot isostatic pressing infiltration treatment.

[0080] In some embodiments, the metal element in the metal protective layer includes any one of Co, Ni or Fe or a combination of at least two of them. Typical but non-limiting combinations include a combination of Co and Ni, a combination of Co and Fe, a combination of Ni and Fe, or a combination of Co, Ni and Fe.

[0081] The method of coating the surface of the pre-sintered body with at least two metal layers in the present invention is a conventional method, as long as the metal layers can be coated on the surface of the pre-sintered body in a non-airtight manner.

[0082] In some embodiments, the at least two metal layers include an innermost high entropy alloy layer and an outermost metal layer. Exemplarily, the method of coating the innermost high entropy alloy layer on the surface of the pre-sintered body includes spraying or alloy thin-walled part casing.

[0083] In certain embodiments, when coating the innermost high entropy alloy layer, the spraying method includes: uniformly spraying a slurry containing the coated high entropy alloy powder on the surface of the pre-sintered body to form the innermost high entropy alloy coating layer.

[0084] In some embodiments, when coating the innermost high entropy alloy layer, the method of coating the alloy thin-walled member includes: preparing the high entropy alloy to be coated into a plurality of thin-walled members having the same shape as the pre-sintered body, coating the plurality of thin-walled members in combination and closely attaching the plurality of thin-walled members to the surface of the pre-sintered body, and coating the plurality of thin-walled members at the interface thereof by The innermost high entropy alloy layer is formed.

[0085] Exemplarily, the method of coating the outermost metal layer includes sleeve coating of a thin-walled metal member.

[0086] In some embodiments, when coating the outermost metal layer, the method of sleeve-arranging the metal thin-walled parts includes: preparing the metal component to be coated into a plurality of thin-walled parts that are consistent with the appearance of the pre-sintered body coated with the inner metal layer, sleeve-arranging the plurality of thin-walled parts in combination and closely attaching to the outer surface of the pre-sintered body coated with the inner metal layer, and the interfaces of the plurality of thin-walled parts are The sleeves are connected to form the outermost metal cladding layer.

[0087] In some embodiments, the melting point of the high entropy alloy layer is m2 It is 600°C-1200°C, for example, it can be 600°C, 800°C, 900°C, 1000°C or 1200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In some embodiments, the metal elements in the high entropy alloy layer include a combination of at least 5 of Al, Fe, Co, Zn, Sn, Ni, Cr, Cu, Mn, Li, Mg or Ti.

[0089] In some embodiments, the volume of the high entropy alloy layer is not less than the total volume of the pores in the pre-sintered body.

[0090] The volume of the high entropy alloy layer is set to be not less than the total volume of the pores in the pre-sintered body, so as to enable the high entropy alloy in the high entropy alloy layer to fully fill the pores in the pre-sintered body, so as to obtain a dense high entropy alloy-ceramic composite material.

[0091] Assuming the density of the high entropy alloy layer to be ρ, the relative density of the pre-sintered body to be D, and the volume of the pre-sintered body to be V, the mass of the required high entropy alloy layer is obtained to be M≥ρ×V×(1-D).

[0092] In order to enable the preparation method provided by the present invention to proceed smoothly, the outermost metal layer can always remain in a solid state during vacuum sintering, hot isostatic pressing infiltration treatment and annealing treatment, thereby avoiding the loss of the high entropy alloy layer due to gravity during the melting process, so as to ensure complete coating and sealing of the pre-sintered body.

[0093] In some embodiments, the metal element in the outermost metal layer includes any one of Ti, Zr, Mo, Nb or Ta, or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ti and Zr, a combination of Mo and Nb, a combination of Mo, Nb and Ta, a combination of Ti, Zr, Mo and Nb, or a combination of Ti, Zr, Mo, Nb and Ta.

[0094] The group of outer metal layers can fully play a protective role. Generally, the thickness of the outermost metal layer increases accordingly with the increase of the volume of the coated high entropy alloy layer.

[0095] In some embodiments, the thickness of the outermost metal layer is 0.1 mm-0.3 mm, for example, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm or 0.3 mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0096] The present invention melts the high entropy alloy layer through vacuum sintering, and causes a diffusion reaction on the surface of the pre-sintered body to form a dense high entropy alloy sealing layer on the surface of the pre-sintered body, thereby achieving complete sealing of the pre-sintered body.

[0097] In some embodiments, the vacuum sintering temperature T2 is higher than the melting point T m2 25°C-50°C higher, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] In some embodiments, the vacuum sintering temperature T2 is higher than the melting point T m1 Lower than 200℃.

[0099] The present invention controls the vacuum sintering temperature T2 to be lower than the melting point T2 of the high entropy alloy layer. m2 The temperature of the vacuum sintering is 25℃-50℃ higher, so that the high entropy alloy layer can be fully melted and diffuse into the surface of the pre-sintered body through the pores and / or interfaces of the pre-sintered body, thereby fully sealing the surface of the pre-sintered body; at the same time, the vacuum sintering temperature T2 is controlled to be higher than the melting point T m1 The temperature is lower than 200℃, which can ensure that the metal protective layer remains in the solid phase, and prevent the carbon, nitrogen, boron or silicon atoms in the ceramic phase from diffusing across the metal protective layer and damaging the high entropy alloy phase structure. Moreover, vacuum sintering is carried out under vacuum conditions, which can ensure that various gas phases fully react and discharge the pre-sintered body before the high entropy alloy melts and seals.

[0100] In some embodiments, the holding time of the vacuum sintering is 0.5h-1h, for example, it can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0101] In some embodiments, the vacuum sintering pressure is 10 -3 Below Pa.

[0102] After vacuum sintering, hot isostatic pressing infiltration treatment is performed. Under the action of gas pressure, the molten high entropy alloy diffuses into the interior of the pre-sintered body along the pores and / or interfaces to fill the pores in the pre-sintered body, thereby obtaining a completely dense high entropy alloy-ceramic composite material.

[0103] In some embodiments, the hot isostatic pressing infiltration treatment is carried out in an inert atmosphere, wherein the gas in the inert atmosphere includes any one of nitrogen, helium or argon, or a combination of at least two of them, typical but non-limiting combinations include a combination of nitrogen and helium, a combination of helium and argon, a combination of nitrogen and argon, or a combination of nitrogen, helium and argon.

[0104] In some embodiments, the pressure of the hot isostatic pressing infiltration treatment is 5MPa-300MPa, for example, it can be 5MPa, 20MPa, 40MPa, 50MPa, 60MPa, 80MPa, 100MPa, 150MPa, 200MPa, 250MPa or 300MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0105] The pressure of hot isostatic pressing infiltration treatment affects the infiltration of the molten high entropy alloy in the pre-sintered body. When the hot isostatic pressing pressure is below 80MPa, as the sintering temperature increases, the diffusion process of the high entropy alloy liquid phase will partially lag behind the densification process of the pre-sintered body, thereby forming a high entropy alloy-ceramic composite material with a gradient distribution of the high entropy alloy phase, that is, the content of the high entropy alloy phase gradually decreases from the surface to the inside; when the hot isostatic pressing pressure is higher than 80MPa and below 300MPa, the diffusion infiltration process of the high entropy alloy liquid phase and the densification process of the pre-sintered body are almost carried out simultaneously, so a high entropy alloy-ceramic composite material with uniform composition can be obtained.

[0106] In some embodiments, the temperature T3 of the hot isostatic pressing infiltration treatment is equal to the temperature T2 of the vacuum sintering.

[0107] In some embodiments, the heat preservation and pressure holding time of the hot isostatic pressing infiltration treatment is 1h-3h, for example, it can be 1h, 1.5h, 2h, 2.5h or 3h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0108] In some embodiments, the annealing temperature T4 is lower than the melting point T m2 .

[0109] The present invention further optimizes the interfacial bonding force between the metal protective layer and the ceramic phase, and between the metal protective layer and the high entropy alloy phase through annealing treatment, thereby improving the strength of the high entropy alloy-ceramic composite material; moreover, it can also effectively reduce the internal stress and improve the toughness of the obtained high entropy alloy-ceramic composite material.

[0110] In some embodiments, the annealing temperature T4 is higher than the melting point T m2 Low 100°C-200°C, for example, it can be 100°C, 120°C, 150°C, 160°C, 180°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some embodiments, the pressure of the annealing process is below 30 Pa.

[0112] In some embodiments, the temperature is increased from room temperature to the annealing temperature T4 at a heating rate of 0.5°C / min-1°C / min, for example, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0113] In some embodiments, at the annealing temperature T4, the holding time is 1h-3h, for example, 1h, 1.5h, 2h, 2.5h or 3h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0114] In some embodiments, the annealing treatment is terminated by cooling the temperature T4 of the annealing treatment to room temperature at a cooling rate of 1°C / min-2°C / min; the cooling rate may be 1°C / min, 1.2°C / min, 1.5°C / min, 1.8°C / min or 2°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0115] In some embodiments, the molding includes at least one of molding, cold isostatic pressing, extrusion molding, injection molding or 3D printing. The present invention does not specifically limit the molding method, as long as a molded body of a desired shape can be obtained. When the desired shape cannot be obtained by one-step molding, the molding also includes cutting.

[0116] In certain embodiments, the degreasing is inert gas negative pressure degreasing or hydrogen positive pressure degreasing.

[0117] In some embodiments, if the shape of the molded body after degreasing is inconsistent with the shape of the target product, cutting processing is performed after degreasing.

[0118] In the present invention, there is no specific restriction on the vacuum pre-sintering temperature T1, and a pre-sintered body with a relative density not exceeding 90% can be obtained. The purpose is to ensure that most of the pores in the pre-sintered body are connected pores, thereby facilitating the infiltration process of the high entropy alloy.

[0119] In some embodiments, the holding time of the vacuum pre-sintering is 1h-3h, for example, 1h, 1.5h, 2h, 2.5h or 3h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0120] In some embodiments, the vacuum pre-sintering pressure is below 30 Pa.

[0121] A certain embodiment of the present invention provides a high entropy alloy-ceramic composite material, and the high entropy alloy-ceramic composite material is prepared by the preparation method described in any embodiment.

[0122] In certain embodiments, when the pressure of the hot isostatic pressing infiltration treatment is greater than 5 MPa and less than 80 MPa, a high-entropy alloy-ceramic composite material with a gradient distribution of high-entropy alloy phase is obtained, that is, the content of the high-entropy alloy phase gradually decreases from the surface to the inside of the high-entropy alloy-ceramic composite material.

[0123] In certain embodiments, when the pressure of the hot isostatic pressing infiltration treatment is higher than 80 MPa and lower than 300 MPa, a high entropy alloy-ceramic composite material with uniform composition is obtained.

[0124] A certain embodiment of the present invention provides an application of a high entropy alloy-ceramic composite material, wherein the high entropy alloy-ceramic composite material is used to prepare molds, cutting tools or wear-resistant parts.

[0125] The high entropy alloy-ceramic composite material is prepared by the preparation method described in any embodiment, or is the high entropy alloy-ceramic composite material described in any embodiment.

[0126] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0127] The technical solution of the present invention will be described in detail below through specific embodiments and comparative examples.

[0128] Examples and Comparative Examples

[0129] Example 1

[0130] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0131] (1) In a nitrogen atmosphere, the raw material powder of the formula amount is placed in a ball mill, and the mixture is ball-milled using cemented carbide grinding balls and anhydrous ethanol. The ball milling time is 48 hours, and the mass ratio of cemented carbide grinding balls to raw material powder is 4:1, to obtain a ceramic phase powder with an average particle size of about 0.2 μm.

[0132] Wherein, in terms of volume percentage, the raw material powder includes 98.45 vol% titanium carbide, 0.55 vol% tantalum carbide and 1 vol% niobium carbide, and the corresponding calculated mass percentages of titanium carbide, tantalum carbide and niobium carbide are 96.91 wt%, 1.57 wt% and 1.52 wt%, respectively.

[0133] (2) A metal protective layer is coated on the surface of the ceramic phase powder particles by chemical coating, and the material of the metal protective layer is cobalt (melting point T m1 1495℃):

[0134] The ceramic phase powder is placed in an activation solution and ultrasonically stirred for 25 minutes, and then placed in a chemical plating solution at a solid-liquid ratio of 250g / L, and kept warm at 85°C until bubbles are generated. Then, chemical plating is performed under ultrasonic stirring at 50°C until no bubbles are generated, and then the powder is washed with deionized water and vacuum dried at 100°C to complete the chemical plating. A ceramic phase powder having a metal protective layer (mass percentage of about 1.31wt%) coated on the surface of the particles is obtained.

[0135] Based on the original formula of the ceramic phase powder and the content of the coated metal protective layer, the theoretical density of the metal-ceramic composite material composed of the two was calculated to be 5.074 g / cm 3 ; The density of titanium carbide, tantalum carbide, niobium carbide and cobalt is 4.93g / cm 3 、14.3g / cm 3 , 7.6g / cm 3 and 8.9g / cm 3 .

[0136] The activation solution includes hydrofluoric acid (mass percentage concentration is 40wt%), ammonium fluoride, nitric acid (mass percentage concentration is 65wt%) and hydrochloric acid (mass percentage concentration is 36wt%); wherein the amounts of hydrofluoric acid, ammonium fluoride, nitric acid and hydrochloric acid in the activation solution are 40mL / L, 3g / L, 30mL / L and 20mL / L respectively.

[0137] The chemical plating solution includes 28 g / L of cobalt sulfate, 25 g / L of sodium hypophosphite, 50 g / L of trisodium citrate and 25 g / L of boric acid.

[0138] (3) The ceramic phase powder with a metal protective layer coated on the particle surface is granulated and a molded body is obtained by cold isostatic pressing at 200 MPa.

[0139] (4) The molded body is degreased in an argon atmosphere and then pre-sintered in vacuum at a pressure of 30 Pa or less to obtain a pre-sintered body having a relative density D of 86%.

[0140] Among them, the vacuum pre-sintering temperature T1 is 1532°C and the holding time is 2h.

[0141] (5) Two metal layers are coated on the surface of the pre-sintered body, and the innermost high entropy alloy layer (melting point T m2 The outermost metal layer is a titanium layer with a thickness of 0.2 mm (melting point T m3 is 1668℃).

[0142] The composition of the high entropy alloy layer is Cu 22.7 Zn 22.7 Mn 22.7 Ni 22.7 Al 9.2 .

[0143] Among them, the density of the high entropy alloy layer is 7.36g / cm 3 According to the relative density D and volume V of the pre-sintered body, the mass M of the high entropy alloy layer is obtained to be ≥ 7.36×V×(1-D).

[0144] (6) At a pressure of 10 -3 Under the condition of less than Pa, vacuum sintering is carried out, and the vacuum sintering temperature T2 = T m2 +35℃=1077℃, keep warm for 0.5h.

[0145] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 10 MPa, a temperature T3 of 1077°C, and a heat preservation and pressure holding time of 3 h to obtain a high entropy alloy-ceramic composite sintered body with a gradient structure.

[0146] (8) The obtained gradient structured high entropy alloy-ceramic composite sintered body is annealed to optimize the interfacial bonding force between the ceramic phase grains and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure of less than 30 Pa, and the temperature is increased from room temperature to T4 = T at a heating rate of 0.5 °C / min. m2-200°C = 842°C, the holding time is 1 hour; then the temperature is lowered from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0147] Example 2

[0148] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0149] The steps for preparing the pre-sintered body in steps (1) to (5) are the same as those in Example 1.

[0150] (6) At a pressure of 10 -3 Vacuum sintering is carried out under conditions below Pa, and the vacuum sintering temperature T2 = T m2 +25℃=1067℃, keep warm for 1h.

[0151] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 5 MPa, a temperature T3 of 1067°C, and a heat preservation and pressure holding time of 3 h to obtain a high entropy alloy-ceramic composite sintered body with a gradient structure.

[0152] (8) The obtained gradient structured high entropy alloy-ceramic composite sintered body is annealed to optimize the interfacial bonding force between the ceramic phase and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure lower than 30 Pa, and the temperature is increased from room temperature to T4 = T at a heating rate of 0.5 °C / min. m2 -100°C = 942°C, the holding time is 1 hour; then the temperature is lowered from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0153] Example 3

[0154] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0155] The steps for preparing the pre-sintered body in steps (1) to (5) are the same as those in Example 1.

[0156] (6) When the pressure is below 10 -3 Vacuum sintering is carried out under the condition of Pa, and the vacuum sintering temperature T2 = T m2 +50℃=1092℃, keep warm for 1h.

[0157] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 70 MPa, a temperature T3 of 1092°C, and a heat preservation and pressure holding time of 3 h to obtain a high entropy alloy-ceramic composite sintered body with a gradient structure.

[0158] (8) The obtained gradient structured high entropy alloy-ceramic composite sintered body is annealed to optimize the interfacial bonding force between the ceramic phase grains and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure lower than 30 Pa, and the temperature is increased from room temperature to T4 = T at a heating rate of 0.5 °C / min. m2 -150°C = 892°C, the holding time is 1 hour; then the temperature is lowered from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0159] Example 4

[0160] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0161] The step parameters in step (1) to step (6) are the same as those in Example 1.

[0162] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 80 MPa, a temperature T3 of 1077°C, and a heat preservation and pressure holding time of 3 h to obtain a high entropy alloy-ceramic composite sintered body with a gradient structure.

[0163] (8) The obtained gradient structured high entropy alloy-ceramic composite sintered body is annealed to optimize the interfacial bonding force between the ceramic phase and the metal protective layer and reduce the internal stress to obtain the high entropy alloy-ceramic composite material; the annealing parameters are the same as those in Example 1.

[0164] Example 5

[0165] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as that of Embodiment 4 except that the pressure of the hot isostatic pressing infiltration treatment is 150 MPa.

[0166] Example 6

[0167] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as that of Embodiment 4 except that the pressure of the hot isostatic pressing infiltration treatment is 300 MPa.

[0168] Example 7

[0169] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as that of Embodiment 5 except that the temperature T2 of vacuum sintering and the temperature T3 of hot isostatic pressing infiltration treatment are 1052°C.

[0170] Example 8

[0171] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as that of Embodiment 5 except that the temperature T2 of vacuum sintering and the temperature T3 of hot isostatic pressing infiltration treatment are 1102°C.

[0172] Example 9

[0173] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as that of Embodiment 5 except that the annealing temperature T4 is 992°C.

[0174] Example 10

[0175] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as that of Embodiment 5 except that the annealing temperature T4 is 792°C.

[0176] Embodiment 11

[0177] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0178] (1) In a nitrogen atmosphere, the raw material powder of the formula amount is placed in a ball mill, and the mixture is ball-milled using cemented carbide grinding balls and anhydrous ethanol. The ball milling time is 48 hours, and the mass ratio of cemented carbide grinding balls to raw material powder is 4:1, to obtain a ceramic phase powder with an average particle size of about 0.2 μm.

[0179] Wherein, in terms of volume percentage, the raw material powder includes 98.45 vol% titanium carbide, 0.55 vol% tantalum carbide and 1 vol% niobium carbide, and the corresponding calculated mass percentages of titanium carbide, tantalum carbide and niobium carbide are 96.91 wt%, 1.57 wt% and 1.52 wt%, respectively.

[0180] (2) A metal protective layer is coated on the surface of the ceramic phase powder particles by chemical coating, and the material of the metal protective layer is nickel (melting point T m1 1455℃):

[0181] The ceramic phase powder was placed in an activation solution and ultrasonically stirred for 25 minutes, placed in a chemical plating solution at a solid-liquid ratio of 250g / L, kept warm at 85°C until bubbles were generated, and then chemically plated at 50°C with ultrasonic stirring until no bubbles were generated, then washed with deionized water and vacuum dried at 100°C to complete the chemical coating; a ceramic phase powder with a metal protective layer (mass percentage of 1.31wt%) coated on the surface of the particles was obtained.

[0182] Based on the original formula of the ceramic phase powder and the content of the coated metal protective layer, the theoretical density of the metal-ceramic composite material composed of the two was calculated to be 5.074 g / cm3 ; The density of titanium carbide, tantalum carbide, niobium carbide and nickel is 4.93g / cm 3 、14.3g / cm 3 , 7.6g / cm 3 and 8.902g / cm 3 .

[0183] The activation solution includes hydrofluoric acid (mass percentage concentration is 40wt%), ammonium fluoride, nitric acid (mass percentage concentration is 65wt%) and hydrochloric acid (mass percentage concentration is 36wt%); wherein the amounts of hydrofluoric acid, ammonium fluoride, nitric acid and hydrochloric acid in the activation solution are 40mL / L, 3g / L, 30mL / L and 20mL / L respectively; and the solvent of the activation solution is deionized water.

[0184] The chemical plating solution includes 28 g / L of nickel sulfate, 25 g / L of sodium hypophosphite, 50 g / L of trisodium citrate and 25 g / L of boric acid.

[0185] (3) The ceramic phase powder with a metal protective layer coated on the particle surface is granulated and a molded body is obtained by cold isostatic pressing at 200 MPa.

[0186] (4) The molded body is degreased in an argon atmosphere and then vacuum pre-sintered at a pressure below 30 Pa to obtain a pre-sintered body with a relative density D of 90%. The vacuum pre-sintering temperature T1 is 1552° C. and is kept for 1 hour.

[0187] (5) Two metal layers are coated on the surface of the pre-sintered body, and the innermost high entropy alloy layer (melting point T m2 The outermost metal layer is a titanium layer with a thickness of 0.1 mm (melting point T m3 is 1668℃).

[0188] The composition of the high entropy alloy layer is Al 80 Li5Mg5Zn5Cu5.

[0189] Among them, the density of the high entropy alloy layer is 3.08g / cm 3 According to the relative density D and volume V of the pre-sintered body, the mass M of the high entropy alloy layer is obtained to be ≥ 3.08×V×(1-D).

[0190] (6) Under pressure 10 -3 Vacuum sintering is carried out under conditions below Pa; the vacuum sintering temperature is T2 = T m2 +50℃=685℃, keep warm for 0.5h.

[0191] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 100 MPa, a temperature T3 of 685°C and a time of 2 h to obtain a high entropy alloy-ceramic composite sintered body with uniform composition.

[0192] (8) The obtained high entropy alloy-ceramic composite sintered body with uniform composition is annealed to optimize the interface bonding force between the ceramic phase and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure of less than 30 Pa, and the temperature is increased from room temperature to T4=T at a heating rate of 0.5°C / min. m2 -150°C = 485°C, and keep warm for 1 hour; then cool from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0193] Example 12

[0194] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0195] (1) In a nitrogen atmosphere, the raw material powder of the formula amount is placed in a ball mill, and the mixture is ball-milled using cemented carbide grinding balls and anhydrous ethanol. The ball milling time is 48 hours, and the mass ratio of cemented carbide grinding balls to raw material powder is 4:1, to obtain a ceramic phase powder with an average particle size of about 0.2 μm.

[0196] Wherein, in terms of volume percentage, the raw material powder includes 98.45 vol% titanium carbide, 0.55 vol% tantalum carbide and 1 vol% niobium carbide, and the corresponding calculated mass percentages of titanium carbide, tantalum carbide and niobium carbide are 96.91 wt%, 1.57 wt% and 1.52 wt%, respectively.

[0197] (2) A metal protective layer is coated on the surface of the ceramic phase powder particles by chemical coating, and the material of the metal protective layer is iron (melting point T m1 is 1538℃):

[0198] The ceramic phase powder was placed in an activation solution and ultrasonically stirred for 25 minutes, then placed in a chemical plating solution at a solid-liquid ratio of 250 g / L, kept warm at 85°C until bubbles were generated, and then chemically plated at 50°C with ultrasonic stirring until no bubbles were generated, then washed with deionized water and vacuum dried at 100°C to complete the chemical plating; a ceramic phase powder having a metal protective layer (mass percentage of 1.17wt%) coated on the surface of the particles was obtained.

[0199] Based on the original formula of the ceramic phase powder and the content of the coated metal protective layer, the theoretical density of the metal-ceramic composite material composed of the two was calculated to be 5.067 g / cm 3; The density of titanium carbide, tantalum carbide, niobium carbide and iron is 4.93g / cm 3 、14.3g / cm 3 , 7.6g / cm 3 and 7.86g / cm 3 .

[0200] The activation solution includes hydrofluoric acid (mass percentage concentration is 40wt%), ammonium fluoride, nitric acid (mass percentage concentration is 65wt%) and hydrochloric acid (mass percentage concentration is 36wt%); wherein the amounts of hydrofluoric acid, ammonium fluoride, nitric acid and hydrochloric acid in the activation solution are 40mL / L, 3g / L, 30mL / L and 20mL / L respectively; and the solvent of the activation solution is deionized water.

[0201] The chemical plating solution includes 28 g / L of ferric sulfate, 25 g / L of sodium hypophosphite, 50 g / L of trisodium citrate and 25 g / L of boric acid.

[0202] (3) granulating the ceramic phase powder with a metal protective layer on the particle surface, and obtaining a molded body by cold isostatic pressing at 200 MPa;

[0203] (4) The molded body is degreased in an argon atmosphere and then vacuum pre-sintered at a pressure below 30 Pa to obtain a pre-sintered body with a relative density D of 82%; the vacuum pre-sintering temperature T1 is 1506° C. and is kept warm for 1 hour.

[0204] (5) Two metal layers are coated on the surface of the pre-sintered body, and the innermost high entropy alloy layer (melting point T m2 The outermost metal layer is a titanium layer with a thickness of 0.1 mm (melting point T m3 is 1668°C);

[0205] The composition of the high entropy alloy layer is AlCoCrFeNiTi 0.5 .

[0206] Among them, the density of the high entropy alloy layer is 6.44g / cm 3 According to the relative density D and volume V of the pre-sintered body, the minimum required mass M of the high entropy alloy layer is 6.44×V×(1-D).

[0207] (6) Under pressure 10 -3 Vacuum sintering is carried out under conditions below Pa; the vacuum sintering temperature is T2 = T m2 +35℃=1223℃, keep warm for 0.5h.

[0208] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 100 MPa, a temperature T3 of 1223°C and a time of 2 h to obtain a high entropy alloy-ceramic composite sintered body with uniform composition.

[0209] (8) The obtained high entropy alloy-ceramic composite sintered body with uniform composition is annealed to optimize the interface bonding force between the ceramic phase and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure of less than 30 Pa, and the temperature is increased from room temperature to T4=T at a heating rate of 0.5°C / min. m2 -150°C = 1038°C, and keep warm for 1 hour; then cool from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0210] Embodiment 13

[0211] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0212] (1) In a nitrogen atmosphere, the formulated raw material powder is placed in a ball mill and ball-milled with silicon carbide grinding balls and anhydrous ethanol for 48 h. The mass ratio of silicon carbide grinding balls to raw material powder is 6:1, and a ceramic phase powder with an average particle size of about 0.6 μm is obtained.

[0213] Wherein, in terms of volume percentage, the raw material powder includes 60 vol% TiN, 25 vol% SiC, and 15 vol% AlN, and the corresponding calculated mass percentages of TiN, SiC, and AlN are 70.92 wt%, 18.05 wt%, and 11.03 wt%, respectively.

[0214] (2) A metal protective layer is coated on the surface of the ceramic phase powder particles by chemical coating, and the material of the metal protective layer is cobalt (melting point T m1 1495℃):

[0215] The ceramic phase powder was placed in an activation solution and ultrasonically stirred for 25 minutes, then placed in a chemical plating solution at a solid-liquid ratio of 250 g / L, kept warm at 85°C until bubbles were generated, and then chemically plated at 50°C with ultrasonic stirring until no bubbles were generated, then washed with deionized water and vacuum dried at 100°C to complete the chemical coating; a ceramic phase powder having a metal protective layer (mass percentage of 1.26wt%) coated on the surface of the particles was obtained.

[0216] Based on the original formula of the ceramic phase powder and the content of the coated metal protective layer, the theoretical density of the metal-ceramic composite material composed of the two is calculated to be 4.489 g / cm 3; The density of TiN, SiC, AlN and Co is 5.24 g / cm 3 、3.2g / cm 3 、3.26g / cm 3 and 8.9g / cm 3 .

[0217] The activation solution includes hydrofluoric acid (mass percentage concentration is 40wt%), ammonium fluoride, nitric acid (mass percentage concentration is 65wt%) and hydrochloric acid (mass percentage concentration is 36wt%); wherein the amounts of hydrofluoric acid, ammonium fluoride, nitric acid and hydrochloric acid in the activation solution are 40mL / L, 3g / L, 30mL / L and 20mL / L respectively; and the solvent of the activation solution is deionized water.

[0218] The chemical plating solution includes 30 g / L of cobalt sulfate, 25 g / L of sodium hypophosphite, 50 g / L of trisodium citrate and 25 g / L of boric acid.

[0219] (3) granulating the ceramic phase powder with a metal protective layer on the particle surface, and obtaining a molded body by cold isostatic pressing at 200 MPa;

[0220] (4) The molded body is degreased in an argon atmosphere and then vacuum pre-sintered at a pressure below 30 Pa to obtain a pre-sintered body with a relative density D of 88%; the vacuum pre-sintering temperature T1 is 1563° C. and is kept warm for 1 hour.

[0221] (5) Two metal layers are coated on the surface of the pre-sintered body, and the innermost high entropy alloy layer (melting point T m2 The outermost metal layer is a niobium layer with a thickness of 0.1 mm (melting point T m3 is 2468°C);

[0222] The composition of the high entropy alloy layer is AlCoCrFeNiTi 0.5 .

[0223] Among them, the density of the high entropy alloy layer is 6.44g / cm 3 According to the relative density D and volume V of the pre-sintered body, the mass M of the high entropy alloy layer is obtained to be ≥ 6.44×V×(1-D).

[0224] (6) Under pressure 10 -3 Vacuum sintering is carried out under conditions below Pa; the vacuum sintering temperature is T2 = T m2 +35℃=1223℃, keep warm for 0.5h.

[0225] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 100 MPa, a temperature T3 of 1223°C and a time of 2 h to obtain a high entropy alloy-ceramic composite sintered body with uniform composition.

[0226] (8) The obtained high entropy alloy-ceramic composite sintered body with uniform composition is annealed to optimize the interface bonding force between the ceramic phase and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure of less than 30 Pa, and the temperature is increased from room temperature to T4=T at a heating rate of 0.5°C / min. m2 -150°C = 1038°C, and keep warm for 1 hour; then cool from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0227] Embodiment 14

[0228] This embodiment provides a method for preparing a high entropy alloy-ceramic composite material, the preparation method comprising the following steps:

[0229] (1) In a nitrogen atmosphere, the formulated raw material powder is placed in a ball mill and mixed using cemented carbide grinding balls and anhydrous ethanol. The ball milling time is 48 hours, and the mass ratio of cemented carbide grinding balls to raw material powder is 4:1, to obtain a ceramic phase powder with an average particle size of about 0.5 μm.

[0230] Among them, in terms of volume percentage, the raw material powder includes 75.5 vol% TiB2, 20 vol% B4C, 2.5 vol% SiC and 2 vol% Mo2C, and the corresponding calculated mass percentages of TiB2, B4C, SiC and Mo2C are 81.64 wt%, 12.06 wt%, 1.91 wt% and 4.39 wt%, respectively.

[0231] (2) A metal protective layer is coated on the surface of the ceramic phase powder particles by chemical coating, and the material of the metal protective layer is cobalt (melting point T m1 1495℃):

[0232] The ceramic phase powder was placed in an activation solution and ultrasonically stirred for 25 minutes, placed in a chemical plating solution at a solid-liquid ratio of 250g / L, kept warm at 85°C until bubbles were generated, and then chemically plated at 50°C with ultrasonic stirring until no bubbles were generated, then washed with deionized water and vacuum dried at 100°C to complete the chemical coating; a ceramic phase powder with a metal protective layer (mass percentage of 1.12wt%) coated on the surface of the particles was obtained.

[0233] Based on the original formula of the ceramic phase powder and the content of the coated metal protective layer, the theoretical density of the metal-ceramic composite material composed of the two was calculated to be 4.227 g / cm 3 The density of TiB2, B4C, SiC, Mo2C and Co is 4.52 g / cm 3 , 2.52g / cm 3 、3.2g / cm 3 , 9.18g / cm 3 and 8.9g / cm 3 .

[0234] The activation solution includes hydrofluoric acid (mass percentage concentration is 40wt%), ammonium fluoride, nitric acid (mass percentage concentration is 65wt%) and hydrochloric acid (mass percentage concentration is 36wt%); wherein the amounts of hydrofluoric acid, ammonium fluoride, nitric acid and hydrochloric acid in the activation solution are 40mL / L, 3g / L, 30mL / L and 20mL / L respectively; and the solvent of the activation solution is deionized water.

[0235] The chemical plating solution includes 30 g / L of cobalt sulfate, 25 g / L of sodium hypophosphite, 50 g / L of trisodium citrate and 25 g / L of boric acid.

[0236] (3) The ceramic phase powder with a metal protective layer coated on the particle surface is granulated and a molded body is obtained by cold isostatic pressing at 200 MPa.

[0237] (4) The molded body is degreased in an argon atmosphere and then vacuum pre-sintered at a pressure below 30 Pa to obtain a pre-sintered body with a relative density D of 84%; the vacuum pre-sintering temperature T1 is 1555° C. and is kept warm for 1 hour.

[0238] (5) Two metal layers are coated on the surface of the pre-sintered body, and the innermost high entropy alloy layer (melting point T m2 The outermost metal layer is a tantalum layer with a thickness of 0.1 mm (melting point T m3 is 2996℃).

[0239] The composition of the high entropy alloy layer is AlCoCrFeNiTi 0.5 .

[0240] Among them, the density of the high entropy alloy layer is 6.44g / cm 3 According to the relative density D and volume V of the pre-sintered body, the mass M of the high entropy alloy layer is obtained to be ≥ 6.44×V×(1-D).

[0241] (6) Under pressure 10 -3 Vacuum sintering is carried out under conditions below Pa; the vacuum sintering temperature is T2 = Tm2 +35℃=1223℃, keep warm for 0.5h.

[0242] (7) Hot isostatic pressing infiltration treatment was carried out under argon atmosphere conditions with a pressure of 100 MPa, a temperature T3 of 1223°C and a time of 2 h to obtain a high entropy alloy-ceramic composite sintered body with uniform composition.

[0243] (8) The obtained high entropy alloy-ceramic composite sintered body with uniform composition is annealed to optimize the interface bonding force between the ceramic phase and the metal protective layer and reduce the internal stress: the annealing treatment is carried out under a pressure of less than 30 Pa, and the temperature is increased from room temperature to T4=T at a heating rate of 0.5°C / min. m2 -150°C = 1038°C, and keep warm for 1 hour; then cool from T4 to room temperature at a cooling rate of 2°C / min to obtain the high entropy alloy-ceramic composite material.

[0244] Comparative Example 1

[0245] This comparative example provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as Example 5 except that the surface of the ceramic phase powder particles is not coated with a metal protective layer.

[0246] Since the particle surface of the ceramic phase powder is not covered with a metal protective layer, the sintering activity is greatly reduced at the same vacuum pre-sintering temperature T1=1532°C as in Example 5. The relative density D of the pre-sintered body obtained in this comparative example is 63%, and the mass M of the high entropy alloy layer is adjusted according to the formula 7.36×V×(1-D).

[0247] Comparative Example 2

[0248] This comparative example provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as Example 5 except that the outermost metal layer is omitted.

[0249] Comparative Example 3

[0250] This comparative example provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as Example 5 except that no annealing treatment is performed.

[0251] Comparative Example 4

[0252] This comparative example provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as Example 5 except that the vacuum pre-sintering temperature T1 is 1563°C.

[0253] Since the vacuum pre-sintering temperature T1=1563° C. is increased, the relative density D of the pre-sintered body obtained in this comparative example is 92%, and the mass M of the high entropy alloy layer is adjusted accordingly according to the formula 7.36×V×(1-D).

[0254] Comparative Example 5

[0255] This comparative example provides a method for preparing a high entropy alloy-ceramic composite material, which is the same as Example 5 except that the temperature T2 of vacuum sintering and the temperature T3 of hot isostatic pressing infiltration treatment are 1500°C.

[0256] The sintering density, hardness, flexural strength and fracture toughness of the high entropy alloy-ceramic composite materials finally obtained in the above embodiments and comparative examples were measured, and the results are shown in Table 1.

[0257] The test method for sintering density is as follows: Since it involves the gradient structure and whether the infiltration is complete, the obtained high entropy alloy-ceramic composite material sample is cut along the center area, the cut surface is ground and polished, and then the entire cut surface is observed using a metallographic microscope or a scanning electron microscope to test whether it is sintered densely.

[0258] The hardness test is carried out in accordance with the national standard GB / T16534-2009 "Test Method for Hardness of Fine Ceramics at Room Temperature". Due to the composition gradient structure involved, based on the sampling method for detecting sintering density, the hardness is measured on the cut surface after grinding and polishing. Assuming that the distance from the edge of the cut surface to the center is L, the edge area is taken as the starting point, and from the edge area to the center area of ​​the sample, four areas with a distance of 0L, L / 3, 2L / 3, and L from the edge are tested respectively. At least 3 values ​​are tested in each area, and the average value is taken.

[0259] The flexural strength test was carried out in accordance with the national standard GB / T4741-1999 "Test Method for Flexural Strength of Ceramic Materials". Since it involves a composition gradient structure, the flexural strength of the gradient structure cannot be tested. Therefore, the flexural strength test was not carried out for the composition gradient structure specimen.

[0260] The fracture toughness test was carried out in accordance with the national standard GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method - Single Edge Precracked Beam (SEPB) Method". Since it involves a composition gradient structure, the fracture toughness of the gradient structure cannot be tested. Therefore, the fracture toughness test was not carried out for the composition gradient structure specimen.

[0261] Table 1 Test results of the embodiments of the present invention and the comparative examples

[0262]

[0263]

[0264] It can be seen from Examples 1 to 6 in Table 1 that as the pressure of the hot isostatic pressing infiltration treatment increases, the composition gradient of the obtained high entropy alloy-ceramic composite material gradually decreases. When the pressure is above 80 MPa, the composition gradient disappears, and a high entropy alloy-ceramic composite material with uniform composition is obtained; at the same time, due to the increase in pressure, it is beneficial to promote the densification of the pre-sintered body, which will cause the high entropy alloy content infiltrated into the pre-sintered body to decrease, and the hardness of the obtained high entropy alloy-ceramic composite material increases, and the fracture toughness decreases.

[0265] From the comparison between Example 5 and Example 7 in Table 1, it can be seen that due to the decrease in the temperature of vacuum sintering and hot isostatic pressing infiltration treatment, the energy of sintering shrinkage is reduced, and the high entropy alloy content in the obtained high entropy alloy-ceramic composite material is slightly increased, resulting in a slight decrease in hardness and flexural strength, while a slight increase in toughness; on the contrary, from the comparison between Example 5 and Example 8 in Table 1, it can be seen that an increase in the temperature of vacuum sintering and hot isostatic pressing infiltration treatment will cause the hardness and flexural strength of the obtained high entropy alloy-ceramic composite material to increase slightly, while the fracture toughness decreases slightly.

[0266] From the comparison between Example 5 and Example 9 and Example 10 in Table 1, it can be seen that if the annealing temperature is too high, the atomic diffusion ability will be enhanced, which may easily lead to changes in the phase structure of the high entropy alloy, while if the annealing temperature is too low, the interface optimization and stress reduction will be insufficient, which will lead to a decrease in the fracture toughness of the obtained high entropy alloy-ceramic composite material.

[0267] From the comparison between Example 5 and Comparative Example 1 in Table 1, it can be seen that due to the lack of a metal protective layer, the phase structure of the high entropy alloy is severely destroyed during vacuum sintering and hot isostatic pressing infiltration treatment, and the hardness, flexural strength and fracture toughness of the obtained high entropy alloy-ceramic composite material are sharply reduced.

[0268] From the comparison between Example 5 and Comparative Example 2 in Table 1, it can be seen that since the outermost metal layer is not coated, the molten high entropy alloy layer is not protected during vacuum sintering, causing it to flow to the lower part of the product and the upper part is not well sealed. The subsequent hot isostatic pressing infiltration treatment cannot sinter it to a dense state.

[0269] From the comparison between Example 5 and Comparative Example 3 in Table 1, it can be seen that due to the lack of annealing treatment, the flexural strength and fracture toughness of the obtained high entropy alloy-ceramic composite material are reduced.

[0270] From the comparison between Example 5 and Comparative Example 4 in Table 1, it can be seen that since the vacuum pre-sintering temperature is increased to be much higher than the melting point of the metal protective layer, the relative density of the pre-sintered body reaches 92%, that is, the pores in the pre-sintered body are almost all closed pores. During the subsequent vacuum sintering and hot isostatic pressing infiltration treatment, the molten high entropy alloy is prevented from diffusing into the interior of the pre-sintered body, resulting in the inability to sinter densely.

[0271] From the comparison between Example 5 and Comparative Example 5 in Table 1, it can be seen that since the temperature of vacuum sintering and the temperature of hot isostatic pressing infiltration treatment are higher than the melting point of the metal protective layer, the high entropy alloy phase structure will also be destroyed, and the flexural strength and fracture toughness of the obtained high entropy alloy-ceramic composite material will be reduced.

[0272] In summary, the present invention coats a metal protective layer on the particle surface of the ceramic phase powder to prevent atoms such as carbon, nitrogen, boron or silicon in the ceramic phase from destroying the high entropy alloy phase structure; then a pre-sintered body with pores is obtained through molding, degreasing and vacuum pre-sintering; then at least two metal layers including an innermost high entropy alloy layer are coated on the surface of the pre-sintered body, the surface of the pre-sintered body is sealed by vacuum sintering, and then hot isostatic pressing infiltration treatment is used to diffuse the molten high entropy alloy along the pores and / or interfaces of the pre-sintered body into the interior of the pre-sintered body, thereby obtaining a dense high entropy alloy-ceramic composite material; wherein, the pressure of the hot isostatic pressing infiltration treatment is controlled to obtain a high entropy alloy-ceramic composite material with a high entropy alloy phase gradient distribution or a high entropy alloy-ceramic composite material with uniform composition; moreover, the application of hot isostatic pressing infiltration treatment also solves the problem that the high entropy alloy bonding phase is easy to agglomerate due to the traditional powder mixing method, and at the same time, it also avoids the problem of incomplete infiltration and being limited by the product's external dimensions.

[0273] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high entropy alloy-ceramic composite material, characterized in that: The preparation method comprises the following steps: A metal protective layer is coated on the surface of the ceramic phase powder particles, and then formed, degreased and vacuum pre-sintered to obtain a pre-sintered body with a relative density not exceeding 90%; Coating at least two metal layers on the surface of the pre-sintered body, and then subjecting the pre-sintered body to vacuum sintering, hot isostatic pressing infiltration treatment and annealing treatment to obtain the high entropy alloy-ceramic composite material; The at least two metal layers include an innermost high entropy alloy layer and an outermost metal layer; The temperature T2 of vacuum sintering, the temperature T3 of hot isostatic pressing infiltration treatment and the temperature T4 of annealing treatment are all lower than the melting point T of the metal protective layer. m1 ; The vacuum sintering temperature T2 is higher than the melting point T m2 ; The melting point T of the outermost metal layer of the at least two metal layers m3 Higher than the melting point T of the metal protective layer m1 .

2. The preparation method according to claim 1, characterized in that: The metal element in the metal protection layer includes any one of Co, Ni or Fe, or a combination of at least two of them.

3. The preparation method according to claim 1, characterized in that: The melting point of the high entropy alloy layer is T m2 It is 600℃-1200℃.

4. The preparation method according to claim 3, characterized in that: The metal elements in the high entropy alloy layer include a combination of at least five of Al, Fe, Co, Zn, Sn, Ni, Cr, Cu, Mn, Li, Mg or Ti; Preferably, the volume of the high entropy alloy layer is not less than the total volume of the pores in the pre-sintered body.

5. The preparation method according to claim 1, characterized in that: The metal element in the outermost metal layer includes any one of Ti, Zr, Mo, Nb or Ta or a combination of at least two thereof; Preferably, the thickness of the outermost metal layer is 0.1 mm-0.3 mm.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The vacuum sintering temperature T2 is higher than the melting point T m2 High 25℃-50℃; Preferably, the vacuum sintering temperature T2 is higher than the melting point T m1 Low than 200℃; Preferably, the holding time of the vacuum sintering is 0.5h-1h; Preferably, the vacuum sintering pressure is 10 -3 Below Pa.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The hot isostatic pressing infiltration treatment is carried out in an inert atmosphere; Preferably, the pressure of the hot isostatic pressing infiltration treatment is 5MPa-300MPa; Preferably, the temperature T3 of the hot isostatic pressing infiltration treatment is equal to the temperature T2 of the vacuum sintering; Preferably, the heat preservation and pressure holding time of the hot isostatic pressing infiltration treatment is 1h-3h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The annealing temperature T4 is lower than the melting point T m2 ; Preferably, the annealing temperature T4 is higher than the melting point T m2 Low 100℃-200℃; Preferably, the pressure of the annealing treatment is below 30 Pa; Preferably, the temperature is raised from room temperature to the annealing temperature T4 at a heating rate of 0.5°C / min-1°C / min; Preferably, the annealing treatment temperature T4 is kept at a temperature of 1h-3h; Preferably, the annealing treatment is terminated by cooling the temperature T4 of the annealing treatment to room temperature at a cooling rate of 1°C / min-2°C / min.

9. A high entropy alloy-ceramic composite material, characterized in that: The high entropy alloy-ceramic composite material is prepared by the preparation method according to any one of claims 1 to 8; Preferably, when the pressure of the hot isostatic pressing infiltration treatment is greater than 5 MPa and less than 80 MPa, a high entropy alloy-ceramic composite material with a high entropy alloy phase gradient distribution is obtained, that is, the content of the high entropy alloy phase gradually decreases from the surface to the inside of the high entropy alloy-ceramic composite material; Preferably, when the pressure of the hot isostatic pressing infiltration treatment is higher than 80 MPa and lower than 300 MPa, a high entropy alloy-ceramic composite material with uniform composition is obtained.

10. An application of a high entropy alloy-ceramic composite material, characterized in that: The high entropy alloy-ceramic composite material is used to prepare molds, cutting tools or wear-resistant parts; The high entropy alloy-ceramic composite material is prepared by the preparation method described in any one of claims 1 to 8, or is the high entropy alloy-ceramic composite material described in claim 9.

Citation Information

Patent Citations

  • Ceramic / high-entropy alloy laminated material and preparation method thereof

    CN108380892A

  • Ceramic phase gradient single-phase high-entropy alloy coating material and preparation method thereof

    CN113564576A

  • High-performance composite binding phase hard alloy and preparation method thereof

    CN118326222A

  • Method for the manufacture of a metal part

    US20110256015A1

  • Hot isostatic pressing (HIP) fabrication of multi-metallic components for pressure-controlling equipment

    US20220184695A1